Improved corrosion resistance achieved in a friction stir processed Mg-5Zn-0.3Ca alloy with fragmented precipitates. (November 2022) - Long, Fei; Liu, Qu; Chen, Gaoqiang; Zhou, Mengran; Shi, Qingyu
Abstract: The microstructure of an as-cast Mg-5Zn-0.3Ca alloy was significantly modified by friction stir processing, which improved the alloy's corrosion resistance. In electrochemical results, the corrosion current density of the FSPed sample at the open circuit potential in 3.5 wt% NaCl aqueous solution decreased to 4.3 μA/cm 2 (about 1/7 that of the as-cast sample). The improved corrosion resistance was attributed to the weakening of galvanic corrosion caused by precipitate fragmentation. In addition, a large number of fine cathodic precipitates tended to accumulate on the corroded surface, thereby forming a denser deposition layer and enhancing the shielding effect against corrosion propagation. Highlights: As a grain refinement method, FSP improves the corrosion current density by two orders of magnitudes to 10 −6 A/cm 2, which is not common in grain refinement treatment. In this paper, FSP is used to modify magnesium alloy to make the second phase finer in size and more uniform in distribution, and the effect of precipitate refinement on the improvement of corrosion resistance is systematically investigated. The effect of precipitate refinement on corrosion resistance enhancement is described from two aspects: the weakening of galvanic corrosion on the corrosion surface and the stronger corrosion shielding on the corrosion depth. The mechanical properties and corrosion resistance are simultaneously improved, which provide a reference for the further investigation of improving comprehensive properties.